IMPLEMENTATION OF THE FAMILY HOPE PROGRAM (CASE STUDY IN THE FIELD OF EDUCATION IN PENGKENDEKAN VILLAGE, SABBANG DISTRICT, NORTH LUWU REGENCY) - Ameliani, Liska; Akib, Haedar; Sakawati, Herlina (Jurnal Aktor, 2025)
This research aims to determine the implementation of the Family Hope Program (Case Study in the Education Sector in Pengkendekan Village, Sabbang Subdistrict, North Luwu Regency). The research uses a descriptive qualitative approach, and data is collected through observation, interviews, and documentation techniques. The data obtained from the research is processed using an interactive analysis model, including data reduction, data presentation, drawing conclusions, and testing conclusions. The results of this research indicate that the implementation of the Family Hope Program in the education component in Pengkendekan Village, Sabbang Subdistrict, North Luwu Regency, has been running well. This is supported by the availability of adequate educational facilities and the active involvement of Family Hope Program facilitators (PKH) in motivating and encouraging parents to optimize their role in their children's education. The factors influencing the implementation of the Family Hope Program (PKH) based on Edward III's theory are communication, resources, disposition, and bureaucratic structure. Of these four factors, communication, disposition, and bureaucratic structure have been effective, while the resource factor has not been fully fulfilled.